Is stiffness related to athletic groin pain? - Gore, S.; Franklyn-Miller, A.; Richter, C.; Falvey, E. C.; King, E.; Moran, K. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Athletic groin pain (AGP) is a common injury prevalent in field sports. One biomechanical measure that may be of importance for injury risk is stiffness. To date however, stiffness has not been examined in AGP. The primary aim was to determine if AGP affects vertical and joint stiffness and if so, whether successful rehabilitation is associated with a change in stiffness. Sixty-five male patients with AGP and fifty male controls were recruited to this study. Assessment included a biomechanical examination of stiffness during a lateral hurdle hop test. Subjects with AGP were tested pre- and post-rehabilitation, while controls were tested once. AGP subjects were cleared for return to play in a median time of 9.14 weeks (5.14-29.0). Stiffness was significantly different at pre-rehabilitation in comparison to controls for four of the ten stiffness values examined; ankle plantar flexor, knee extensor, hip abductor and vertical stiffness (p < 0.05, D = 0.36-0.79). Despite clearance for return to play, of these four variables, only hip abductor stiffness changed significantly from pre- to post-rehabilitation (p = 0.05, D = 0.35) to become non-significantly different to the uninjured group (p = 0.18, D = 0.26). These findings suggest that hip abductor stiffness may represent a target for AGP rehabilitation. Conversely, given the clearance for return to play, the lower sagittal plane and vertical stiffness in the AGP group in comparison to the uninjured controls likely represents either a compensatory mechanism to reduce risk of further injury or is a consequence of neuromuscular detraining.